A randomized clinical trial of genetic testing and personalized risk counselling in patients with type 2 diabetes receiving integrated care -The genetic testing and patient empowerment (GEM) trial. (July 2022) - Ma, Ronald Ching Wan; Xie, Fangying; Lim, Cadmon King Poo; Lau, Eric Siu Him; Luk, Andrea On Yan; Ozaki, Risa; Cheung, Grace Pui Yiu; Lee, Heung Man; Ng, Alex Chi Wai; Li, Heung Wing; Wong, Carmen Ka Man; Wong, Samuel Yeung Shan; et al.
Highlights: In a randomized clinical trial, providing personalized risk prediction based on genetic markers of diabetic kidney disease on top of standard integrated care (including risk prediction based on clinical risk factors) led to improvement in target attainment, with no difference between the two groups. Subjects who received genetic counselling had higher diabetes empowerment, with improved positive attitude and reduced diabetes distress. Subjects with high GRS had the highest increments in attaining multiple treatment targets accompanied by improvement in self-management. Future studies on the implementation of precision medicine in diabetes need to include assessment of patient reported outcomes, as well as evaluate how best to communicate risk to patients to improve patient empowerment and long-term outcome. Abstract: Aims: We evaluated the effect of personalized risk counseling incorporating clinical and genetic risk factors on patient empowerment and risk factor control in diabetes. Methods: Patients with type 2 diabetes (T2D) with suboptimal glycaemic control (HbA1c ≥ 7.5%) were randomized to a genetic counselling (GC) or control group. All patients underwent genetic testing for alleles at three loci associated with diabetic complications. The GC group received additional explanation of the joint associations of genetic and modifiable risk factors on risk of complications. All patients were reassessed at 12 months including validated questionnaires for patient reported outcomes. The primary outcome was proportion of patients reaching ≥ 3 of 5 predefined treatment targets (HbA1c < 7%, BP < 130/80 mmHg, LDL-C < 2.6 mmol/L, Triglyceride < 2.0 mmol/L, use of renin-angiotensin system inhibitors). Secondary outcomes included new-onset chronic kidney disease or microalbuminuria and patient reported outcome measures. Results: A total of 435 patients were randomized and 420 patients were included in the modified intention-to-treat analysis. At 12 months, the proportion of patients who attained ≥ 3 targets increased from 41.6% to 52.3% in the GC group (p = 0.007) versus 49.5% to 62.6% in the control group (p = 0.003), without between-group difference. Both groups had similar reduction in HbA1c, LDL-C and increased use of medications. In per protocol analysis, the GC group had higher diabetes empowerment, with reduced diabetes distress. In the GC group, the greatest improvement in positive attitude and self-care activities was observed in the intermediate to high genetic risk score (GRS) groups. Conclusions: In patients with T2D receiving integrated care, additional counselling on genetic risk of complications did not further improve risk factor control, although the improvement in self-efficacy warrants long-term evaluation.